GENETIC VARIABILITY AND CHARACTER ASSOCIATION FOR AGRONOMIC TRAITS IN HYBRID RICE (Oryza Sativa L.) - Hasan, M. J.; Kulsum, M. U.; Akter, A.; Masuduzzaman, A. S. M.; Ramesha, M. S. (Bangladesh Journal of Plant Breeding and Genetics, 2013)
Twenty four hybrid rice varieties of diverse origin were studied for genetic variability, correlation and path analysis under medium high land of Gazipur. The PCV values were greater than GCV, revealing little influence of environment in character expression. High values of heritability along with moderate genetic advance were observed for panicle/m2, days to 50% flowering and plant height. Grain yield showed positive significant association with number of effective tillers/hill, panicle/m2, spikelet fertility and thousand grain weight at both genotypic and phenotypic levels. Same traits had highest significant positive effect on yield. DOI: http://dx.doi.org/10.3329/bjpbg.v24i1.16999